Selection of microhabitats, plants, and plant parts eaten by a threatened tortoise: observations during a superbloom - Jennings, W. Bryan; Berry, Kristin H. (Frontiers in Amphibian and Reptile Science, 2023)
Populations of the threatened desert tortoise (Gopherus agassizii) continue to decline throughout the geographic range, in part because of degraded and fragmented habitats in the Mojave and western Sonoran deserts. The species is herbivorous and highly selective in choice of plant species. To increase options for recovery, we analyzed behaviors, patterns of movements while foraging, and parts of plants consumed during a superbloom. We characterized foraging routes and the habitat strata and microhabitats where tortoises traveled to eat preferred wildflower species. Tortoises walked one foraging route per day in early spring, often switched to two routes per day in middle and late spring with rise of midday temperatures. They chose habitat strata (primarily hills and ephemeral stream channels) and three of seven microhabitats for foraging on preferred food plants. Preferred microhabitats were intershrub open space and small (1–2 m wide) ephemeral stream channels. They rarely took bites of forbs growing under and in the dripline of shrubs or nonnative forbs and grasses. Tortoises typically did not select specific plant parts to eat but important exceptions occurred. For example, they usually ignored the inflorescences of the annual Eremothera boothii and, when eating the non-native annual Erodium cicutarium, tended to focus on fruits. All such information aids recovery efforts to restore declining tortoise populations.